Program Pendampingan Intensif Pengelolaan Keuangan Mikro untuk Komunitas Rentan Ekonomi - Safiatuddin, Sri (BA: Jurnal Pengabdian kepada Masyarakat, 2024)
This intensive financial coaching program aims to improve financial literacy and promote behavioral changes in financial management among economically vulnerable communities. Employing a mixed-methods approach with a sequential explanatory design, data were collected through pre- and post-program surveys and in-depth interviews. The findings indicate a significant increase in financial knowledge, budgeting practices, saving habits, and financial record-keeping. Participants also reported an increased sense of financial control and security. However, challenges such as unstable income and limited access to formal financial services remain. These results highlight the effectiveness of sustained coaching in enhancing financial resilience in vulnerable communities and suggest the need for integration with broader economic empowerment strategies.